Network Societies: Neoliberal Materials for an Exploratory Theory - Mlađenović, Nikola (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
The paper examines different notions of knowledge in an information society and argues that Manuel Castells’ theory of the network society should be positioned between the concepts of postindustrial and knowledge society. Castells explicitly relies on Daniel Bell’s conservative definition and discards Fritz Machlup’s understanding of knowledge. This puts Castells in a difficult position when it comes to evaluation of the network society’s social structure. Neoliberal anti-scientific and anti-Enlightenment definition of knowledge questions the fundamental split between the Net and the Self, the tension between information and social networks. Mundane, ephemeral knowledge of the common people is at the center of neoliberal perspective of market and culture, in contrast with the concept of the network society. The neoliberal knowledge problem is examined on three levels of Castells’ proposed struggle between information and social networks: power of identity vs communication power, mass self-communication vs hypertext meta-language; and culture of real virtuality vs the public mind.
Keywords: network society; information society; Manuel Castells; media; knowledge